Effect of follicular wave stage on potential fertility predictors and their repeatability coefficient in prepubertal Bos indicus (Nellore) and Bos taurus (Caracu) heifers - Bevilaqua, J. R. [UNESP]; Rodrigues, N. N. [UNESP]; Rossi, G. F. [UNESP]; Pupin, M. A.F. [UNESP]; Silva, M. O.; Borges, M. S.; Fernandes, L. G. [UNESP]; Mercadante, M. E.Z.; Monteiro, F. M. [UNESP]; Oliveira, M. E.F. [UNESP] (Elsevier, 2022)
In an attempt to develop accessible methods for the precocious individual selection based on phenotypic attributes related to reproductive superiority, this study evaluated the effects of follicular wave stages (emergence and dominance) and the repeatability coefficients of potential fertility predictors (vulvar morphometry, uterine biometry, echogenicity and echotexture, ovarian biometry, and antral follicle count – AFC) in two breeds of purebred prepubertal heifers. Nellore (n = 30) and Caracu (n = 28) heifers were submitted to a sequence of 11 evaluations conducted every 48 h (D0 – random day of the antral follicular wave until D20) to study potential fertility indicators under natural conditions. The data obtained were compared according to breed and follicular wave stage. Statistical analysis included the fixed effects of breed, evaluation day, and their statistical interaction and was performed using MIXED, GENMOD, GLM, and CORR procedures of the SAS program. Breed was found to influence rima height, ovarian area, and AFC, which were greater in Nellore heifers (P < 0.02). The follicular wave stage also influenced most of the potential predictors, highlighting AFC which was higher in the presence of a dominant follicle in both breeds (P < 0.0001). The repeatability coefficients for vulvar width (0.76 and 0.66), ovarian area (0.70 and 0.62), and AFC (0.76 and 0.74) were considered to be high in Nellore and Caracu heifers, respectively. Only ovarian biometry was able to predict AFC (Pearson correlation coefficient ≥ 0.66; P < 0.0001) in prepubertal heifers. The results indicate that most of the phenotypic reproductive parameters analyzed can be characterized throughout prepuberty using a single measure since they are intrinsic attributes of the individual.
Keywords: Antral follicular count; Biometry; Ovarian dynamics; Prepuberty; Reproductive performance